The molecular profile of the inflammatory process differs among various neurodevelopmental disorders with or without cognitive component: A hypothesis of persistent systemic dysfunction and hyper-resolution - Madrid, Miriam; Bojalil, Rafael; Brianza-Padilla, Malinalli; Zapoteco-Nava, Jasbet; Márquez-Velasco, Ricardo; Rivera-González, Rolando (Frontiers in Pediatrics, 2023)
Introduction. Challenges of diverse origin in childhood can alter the growth and development of the central nervous system, affecting structures and functions. As a consequence of the damage suffered during the perinatal period, long periods of dysfunctionality may occur, such as regulatory disorders, which may result in remaining in a process of low-grade inflammation. We previously found that perinatal risks and neurological signs are associated with long-term changes in circulating concentrations of molecules of the inflammatory process, findings that are consistent with the postulate that long periods of dysfunction may condition long-lasting low-grade inflammation or parainflammation. The aim of this study was to assess whether different expressions of neurological disorders show variations in their inflammatory molecule profiles or whether there is a common pattern. Methods. We included screening for a) caregiver-perceived risk detection of regulatory disturbances, using the DeGangi instrument; b) dysautonomia or asymmetries, through neurodevelopmental assessments; c) cognitive developmental disturbances (using the Bailey instrument). We assessed protein molecules on a multiplex system, and lipid molecules by ELISA. Results. We found a similar, although not identical, pattern of cytokine profiles with the presence of risk of regulatory disturbances, dysautonomia and asymmetries; but an opposite inflammatory profile was associated with cognitive impairment. Discussion. Our results suggest that there are diverse, probably limited, molecular footprints associated with impaired function, and that these footprints may depend on the response requirements necessary to adjust to the altered internal environment. Here we propose a theoretical model that suggests possible scenarios for inflammatory outcomes associated with chronic challenges.